Ownership and Governance of Malaysian Firms and Their Impact on Firm Performance. A Preliminary Study - Ramli, Ainon (International Review of Management and Marketing, 2019)
In the last twenty years, the issue of firm ownership has received great attention, especially in developed countries such as the United States, the United Kingdom, and European countries. The issue of ownership structures has aroused public concern in Malaysia, one of the emerging markets, especially after the 1997 Asian financial crisis. Issues related to corporate governance are not novel or recent because they occur simultaneously with the birth of the company. In the aftermath of the 1997 financial crisis, governance of firms became an attractive topic for researchers because ownership in Malaysia varies by management, concentration, and foreign or government ownership, thus, it will have different impacts on firm performance. However, there is a lack of empirical studies that have been conducted on firm ownership, governance, and corporate performance in the Malaysian context. These issues need more attention from researchers to contribute to the growing literature and for practical relevance to Malaysian firms. Keywords: Ownership structure, corporate governance, firm performance. JEL Classifications: M1, M10 DOI: https://doi.org/10.32479/irmm.7222